The effects of the Covid-19 Pandemic on the mental health and subjective wellbeing of workers: An event study based on high-frequency panel data - Julia Schmidtke; Clemens Hetschko; Ronnie Schöb; Gesine Stephan; Michael Eid; Mario Lawes (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2021)
Using individual monthly panel data from December 2018 to December 2020, we estimate the impact of the Covid-19 pandemic and two lockdowns on the mental health and subjective well-being of German workers. Employing an event-study design using individual-specific fixed effects, we find that the first and the second wave of the pandemic reduced workers' mental health substantially. Momentary happiness and life satisfaction also decline in response to Covid-19, but to a smaller extent. We observe adaptation in our study outcomes between waves of the pandemic. This applies to a lesser extent to indicators of well-being in certain areas of life, such as satisfaction with the job and with leisure, which are negatively affected, too. Women do not seem to suffer greater well-being losses than men. However, workers in the German short-time work scheme are particularly negatively affected. Our results imply that increased anxiety about the future and restricted personal freedoms are among the drivers of the well-being impact of the pandemic. – – Der Beitrag untersucht die Auswirkungen der Covid-19-Pandemie und zweier Lockdowns auf die psychische Gesundheit und das subjektive Wohlbefinden von Beschäftigten in Deutschland. Hierzu wird mit Daten eines monatlichen Panels von Individualdaten von Dezember 2018 bis Dezember 2020 ein Event-Study-Design mit individualspezifischen Fixeffekten geschätzt. Die Ergebnisse zeigen, dass die erste und die zweite Welle der Pandemie die psychische Gesundheit von Arbeitnehmerinnen und Arbeitnehmern erheblich reduziert hat. Auch das momentane Glücksempfinden und die Lebenszufriedenheit nehmen als Reaktion auf Covid-19 ab, jedoch in geringerem Maße. Dabei ist zwischen den Wellen der Pandemie Adaption zu beobachten. Dies gilt in geringerem Maße für Indikatoren des Wohlbefindens in bestimmten Lebensbereichen, wie die Zufriedenheit mit der Arbeit und mit der Freizeit, die ebenfalls negativ beeinflusst werden. Frauen scheinen keine größeren Verluste an Wohlbefinden zu erleiden als Männer. Beschäftigte in Kurzarbeit sind jedoch besonders stark betroffen. Die Ergebnisse deuten darauf hin, dass größere Sorgen in Bezug auf die Zukunft und eingeschränkte persönliche Freiheiten zu den Treibern für die Auswirkungen der Pandemie auf das Wohlbefinden gehören.
Keywords: I31; I19; 330; Affective well-being; app-based survey data; Covid-19 pandemic; depression; German Job Search Panel; life satisfaction